Teaching resources for the teaching of microbiology. a proposal for teacher training. - Rocío Pérez Escoba; Cecilia María Martínez Delgado; Ana Julia Hoyos González (Universidad del Magdalena, 2015)
The didactic action is necessarily a combined fact, an dialogic action, centered in a precise object, that they wants to become trained; for it is required it the understanding they give what happens in the classroom, without speaking for speak fact they gives to make it, but recognizing all those transactions that are developed in a moment and given space, called knowledge. Problems  to the teaching in the higher education, they allow to respond questions related with the way like this is exercised in a context, understanding that many give the educational ones has formation in the field to own discipline, more no in pedagogic sciences. These considerations allowed to meditate on other alternatives we give teaching the Microbiology, to investigate on other models we formed centered in the student, don't who passive fellow but as constructor itself and constructor for the society.